Can micronutrient training create women's demand for high-zinc rice? The case of Bangladesh - Valera, Harold Glenn (International Rice Research Institute, 2018)
Presented by Harold Glenn Valera (IRRI) on 19 October 2018, as part of the webinar 'Can micronutrient training create women's demand for high-zinc rice? The case of Bangladesh'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the International Rice Research Institute (IRRI).